TRENDS IN THE FINANCING OF THE COMMUNAL SECTOR IN THE CONTEXT OF POST-WAR RECOVERY - Kokhan , I.V.; Dmytrovska , V.S. (The actual problems of regional economy development, 2023)
Ensuring a high standard of living of the population, meeting the necessary needs of citizens in comfortable housing, energy, transport, and services are the key tasks of a socially oriented economy. Adequate satisfaction of these needs is possible only under the conditions of uninterrupted and efficient functioning of utility enterprises, and the quality and efficiency of the activity of utility enterprises directly depends on their financial condition. Especially now in the conditions of decentralization, it is relevant to study the issues of functioning, development and financial support, the financial condition of communal enterprises. The problems and prospects of restoring the communal sphere of Ukraine during and after the end of the Russian war against Ukraine are considered. Russia's full-scale invasion of Ukraine led to large human casualties, massive displacement of the population, and significant infrastructure damage. The impact on economic activity was also enormous: real GDP fell sharply, inflation soared, trade was severely disrupted, and the budget deficit rose to unprecedented levels. The main events and development of the economy during the martial law in the state were analyzed, the problems were identified and the optimal conditions for the future development of the communal sphere were substantiated. Already existing plans for the restoration of Ukraine's infrastructure after the end of the war are analyzed and other possible options for the development of the reconstruction of the utility sector in the context of the international education of the European Union countries are predicted. The purpose of the article is to study the main directions of theoretical foundations and practical recommendations for the formation and use of financial resources of communal enterprises and the development of scientific and practical recommendations for improving the management of financial resources of communal enterprises in Ukraine. The following methods of scientific research were applied during the formation of the analytical basis for evaluating the effectiveness of financial management of utility companies: formalization, measurement, statistical, analytical, comparison, sociological, structural and logical analysis. The methods of idealization, forecasting, generalization, modeling, methods of quantitative and qualitative research were used to determine the directions of modernization of the management of the finances of communal enterprises in the conditions of post-war recovery.